Determining transient patterns in parallel-connected transformers of different capacities - Panchenko, Anatoliy; Boklah, Iryna; Musairova, Yulia; Honcharov, Volodymyr; Kuravska, Nadia (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates transient processes and current distribution in parallel-connected transformers on a common load. The task addressed relates to the fact that the mathematical description of processes is performed in instantaneous current values, in which the parameters used are widely known on the one hand while rarely used in practice on the other. This approach allows a single system of differential equations to describe most operating modes of transformers, as well as transitions between them at the same time. That, in turn, makes it possible to obtain separate instantaneous values of currents for each transformer and the balancing current between them. That is, to control the load distribution between transformers, energy losses, both under steady-state and transient modes. It is almost impossible to acquire such data with control and measuring equipment. This work proves that the ratio of active and reactive components of the windings should also be taken into account. Short-circuit voltages can be the same while the ratio between active and reactive resistances of the windings can be different. And this affects the transient processes and the balancing current. Such results were achieved by compiling differential equations of parallel-connected transformers and the load. It was established that the total duration of transients decreases when transformers are connected in parallel. At the same time, the duration of transients of the balancing current does not depend on the load at all but only on the parameters of the transformer and on the moment of switching. The studies were conducted on transformers TM-180/10 and TM-530/10; it was confirmed that the balancing currents take small values, compared to the load currents, but they are on the same order of magnitude as the magnetizing currents and can distort the magnetizing curve, which provokes higher harmonics. For the specified transformers, the duration of transients on the balancing currents, under certain conditions, was more than 1 second, and when a short circuit occurs on the common buses, more than 2 seconds. This study showed that it is possible to measure most of the parameters for the specified system of equations on a real transformer. It also becomes possible to calculate them according to the specifications and compare the operation of the models under different modes. This could allow a more objective assessment of the technical condition of the transformer